Intersectoral collaboration: a novel path to promote community health promotion - Sarker, Malabika; Joarder, Taufique (© 2012 Global Health Promotion, 2016)
This editorial was published in Global Health Promotion [© The Author(s) 2012] and the definite version is available at: http://ped.sagepub.com/content/19/4/7.full.pdf